Radiation from plasma due to parametric excitation of convective cells - Panchenko, V.G. (Вопросы атомной науки и техники, 2018)
On the basis of the fluctuations kinetic theory the process of plasma radiation is studied when the transformation
of an longitudinal Langmuir wave into the transverse electromagnetic wave occurs. We consider the parametric
decay of upper hybrid pump wave into the daughter wave and modified convective cells. The transformation
coefficient is obtained. For typical ionospheric plasma parameters we show that the pump wave term can exceed by
several orders of magnitude the analogous one for the case of stable plasma. The intensity of transverse waves
radiation from turbulent plasma is calculated and its dependence on convective cells frequency and damping rate is
found. На основі кінетичної теорії флуктуацій вивчається процес випромінювання із плазми під час
трансформації повздовжньої ленгмюрівської хвилі в поперечну електромагнітну. Розглянуто параметричний
розпад верхньогібридної хвилі накачки на дочірню хвилю і модифіковані конвективні комірки. Отримано
вираз для коефіцієнта трансформації. Для типових параметрів іоносферної плазми показано, що член,
обумовлений полем накачки, може перевищувати відповідну величину для випадку спокійної плазми на
декілька порядків. Обчислена інтенсивність випромінювання поперечної хвилі із турбулентної плазми та
знайдено її залежності від частоти і декременту загасання конвективних комірок. На основе кинетической теории флуктуаций изучается процесс излучения из плазмы при трансформации
продольной ленгмюровской волны в поперечную электромагнитную. Рассмотрен параметрический распад
верхнегибридной волны накачки на дочернюю волну и модифицированные конвективные ячейки. Получено
выражение для коэффициента трансформации. Для типичных параметров ионосферной плазмы показано,
что член, обусловленный полем накачки, может превышать соответствующую величину для случая
спокойной плазмы на несколько порядков. Вычислена интенсивность излучения поперечной волны из
турбулентной плазмы и найдены ее зависимости от частоты и декремента затухания конвективных ячеек.